Poznańskie wydanie Traktatu o modlitwie i medytacji św. Piotra z Alkantary z roku 1627 - Tomczak, Salezy Bogumił (Ecclesia. Studia z Dziejów Wielkopolski, 2018)
St. Peter of Alcantara (1499-1562) is among the most outstanding representatives of the golden age of Spanish mysticism. His greatest merit lay in popularizing the theological principles of prayer in his “Treatise on Prayer and Meditation”, written in simple language. It is a compendium of the author’s profound reflections and advice on prayer which he derived from the practice of his own life, his experience as spiritual director and confessor, and from the study of ascetic works. Thanks to the efforts of the Poznań Bernardines this modest book appeared in print in Poznań in 1627 in the renowned printing house of Jan Wolrab. It is a format 12o print, bound in pig skin without any ornaments, comprising 409 pages plus an index. The text contains three engravings. One of them shows St. Francis of Assisi receiving the stigmata on Mount Alvernia on 14 September 1224. There are two more engravings in the book, which confirms the opinion that Jan Wolrab paid attention to the aesthetic side of his prints.